2006
DOI: 10.1534/genetics.106.055442
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Gene Recruitment Reveals Adaptive Reprogramming of Gene Regulation in Yeast

Abstract: The recruitment of a gene to a foreign regulatory system is a major evolutionary event that can lead to novel phenotypes. However, the evolvability potential of cells depends on their ability to cope with challenges presented by gene recruitment. To study this ability, we combined synthetic gene recruitment with continuous culture and online measurements of the metabolic and regulatory dynamics over long timescales. The gene HIS3 from the histidine synthesis pathway was recruited to the GAL system, responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

13
117
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(130 citation statements)
references
References 33 publications
13
117
0
Order By: Relevance
“…Such events are well documented by comparative genomic studies and were reported to drive significantly the evolution of gene regulation [ (Carroll et al, 2001;Wilkins, 2002;Davidson, 2006) also, see the discussions in Alonso and Wilkins (2005); Stern and Orgogozo (2008); Erwin and Davidson (2009)]. In our experiments, a strain of the yeast Saccharomyces cerevisiae was engineered to recruit the gene HIS3, an essential enzyme from the histidine biosynthesis pathway, exclusively to the GAL system that is responsible for galactose utilization (Stolovicki et al, 2006). The arbitrary regulatory linkage between these two evolutionary conserved and highly specific modules was stressful, challenging and created incompatibilities in gene expression (Stolovicki et al, 2006).…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…Such events are well documented by comparative genomic studies and were reported to drive significantly the evolution of gene regulation [ (Carroll et al, 2001;Wilkins, 2002;Davidson, 2006) also, see the discussions in Alonso and Wilkins (2005); Stern and Orgogozo (2008); Erwin and Davidson (2009)]. In our experiments, a strain of the yeast Saccharomyces cerevisiae was engineered to recruit the gene HIS3, an essential enzyme from the histidine biosynthesis pathway, exclusively to the GAL system that is responsible for galactose utilization (Stolovicki et al, 2006). The arbitrary regulatory linkage between these two evolutionary conserved and highly specific modules was stressful, challenging and created incompatibilities in gene expression (Stolovicki et al, 2006).…”
mentioning
confidence: 81%
“…In our experiments, a strain of the yeast Saccharomyces cerevisiae was engineered to recruit the gene HIS3, an essential enzyme from the histidine biosynthesis pathway, exclusively to the GAL system that is responsible for galactose utilization (Stolovicki et al, 2006). The arbitrary regulatory linkage between these two evolutionary conserved and highly specific modules was stressful, challenging and created incompatibilities in gene expression (Stolovicki et al, 2006). The cells had not exercised regulation of HIS3 by carbon sources availability along their history, so a substantial adaptive response was required for them to survive in a medium lacking histidine.…”
mentioning
confidence: 99%
See 3 more Smart Citations